2019
DOI: 10.1590/1414-431x20199093
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of risk factors for low 1-minute Apgar scores in term neonates

Abstract: The current study was designed to investigate the perinatal risk factors for low 1-min Apgar scores in term neonates. We retrospectively analyzed the maternal and neonatal clinical data of 10,550 infants who were born through vaginal delivery from 37 weeks 0 days to 41 weeks 6 days of single gestation from January 2013 to July 2018. Because the 1-min Apgar score reflects neonatal status at birth, we analyzed the risk factors for low (score <7) 1-min Apgar scores through logistic regression. Among these 10,550 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…This means that as Apgar score decreased, neonatal admission was increased. This comes in agreement with Yang et al, [9] who found that, neonates who had low 1-min Apgar scores were more frequently admitted to the neonatology department and in agreement with Salustiano et al, [10] who found that, in infants with low Apgar score at 5 min, there is increased risk of admission to neonatal intensive care unit.…”
Section: Discussionsupporting
confidence: 92%
“…This means that as Apgar score decreased, neonatal admission was increased. This comes in agreement with Yang et al, [9] who found that, neonates who had low 1-min Apgar scores were more frequently admitted to the neonatology department and in agreement with Salustiano et al, [10] who found that, in infants with low Apgar score at 5 min, there is increased risk of admission to neonatal intensive care unit.…”
Section: Discussionsupporting
confidence: 92%
“…This score has been used as a predictive index for neonatal mortality and morbidity, and for later neurologic or developmental disability ( 51 ). Numerous factors can influence Apgar score, such as maternal education and BMI, gestational age, pathological obstetrics, longer duration of the second stage of labor, neonatal weight and meconium-stained amniotic fluid ( 52 ). The present results suggested that 1-min Apgar score was a risk factor for respiratory assistance in premature infants, indicating that weight control in pregnant women, reduction of the preterm birth and other measures may reduce the use of ventilators.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of MSAF (meconiumstained amniotic fluid) was associated with a low Apgar score due to the presence of meconium aspiration syndrome (Yang et al, 2019). Meconium-mixed amniotic fluid is a commonly observed phenomenon.…”
Section: The Effect Of Low Birth Weight On the Risk Of Asphyxiamentioning
confidence: 99%